2017
DOI: 10.1080/03007995.2017.1334638
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of effectiveness and safety of treatment with apixaban vs. other oral anticoagulants among elderly nonvalvular atrial fibrillation patients

Abstract: In the real-world setting after controlling for differences in patient characteristics, apixaban is associated with significantly lower risk of S/SE and MB than rivaroxaban and warfarin, and a trend towards better outcomes vs. dabigatran among elderly NVAF patients in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 24 publications
8
41
1
7
Order By: Relevance
“…However, other studies also reported bleeding risks to be higher among rivaroxaban patients than among patients using dabigatran [38][39][40][41], a finding that was observed for other bleeds but not gastrointestinal bleeding in our study; this could, however, be due to different definitions of bleeding being used. As in this study, several other studies reported no differences in bleeding events between apixaban and dabigatran [36,37,39]; most other studies also did not find any differences with regard to haemorrhagic stroke.…”
Section: Figuresupporting
confidence: 62%
See 3 more Smart Citations
“…However, other studies also reported bleeding risks to be higher among rivaroxaban patients than among patients using dabigatran [38][39][40][41], a finding that was observed for other bleeds but not gastrointestinal bleeding in our study; this could, however, be due to different definitions of bleeding being used. As in this study, several other studies reported no differences in bleeding events between apixaban and dabigatran [36,37,39]; most other studies also did not find any differences with regard to haemorrhagic stroke.…”
Section: Figuresupporting
confidence: 62%
“…In this study, no significant differences between DOACs were found in the risks of strokes, systemic embolism, transient ischaemic attacks or combinations thereofin line with the majority of previously published research. Other observational studies also found no differences in the risk of stroke between dabigatran and rivaroxaban [38], the combination of stroke/systemic embolism between apixaban and dabigatran [37] or between any of the DOACs [41], or a composite outcome of stroke, systemic embolism and death across all DOACs [39], principally confirming conclusions made based on indirect comparisons between DOACs using clinical trial data [12][13][14]. Unlike the results with regard to these primary outcomes, which have shown high agreement across studies, findings relating to secondary outcomes were nevertheless varied.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Apixaban received regulatory approval in Japan in 2012 for the prevention of ischemic stroke and SE in patients with NVAF. To date, the real‐world safety and effectiveness of apixaban in patients with NVAF have been assessed in retrospective claims database studies both outside of Japan and in Japan . However, data are still limited in Japanese NVAF patients.…”
Section: Introductionmentioning
confidence: 99%